DNA polymerase delta from embryos of Drosophila melanogaster. - Chiang, C S (1993)
We have purified a DNA polymerase activity from 0- to 2-hr embryos of Drosophila melanogaster to near homogeneity. The purified enzyme consists of a single 120-kDa polypeptide, which contains polymerase and 3'-->5' exonuclease activities. Exonuclease activity is inhibited by deoxynucleoside triphosphates, suggesting that the polymerase and exonuclease activities are coupled. The polymerase is more active with poly(dA-dT) than with activated DNA or poly(dA)/oligo(dT) as template. It shows a low degree of processivity with poly(dA)/oligo(dT). The polymerase is sensitive to aphidicolin and carbonyldiphosphonate but resistant to N2-[p-(n-butyl)phenyl]-2-deoxyguanosine triphosphate, 2-[p-(n-butyl)anilino]-2-deoxyadenosine triphosphate, and dideoxythymidine triphosphate. The 120-kDa polypeptide can be distinguished from the large subunit of Drosophila DNA polymerase alpha on the basis of the peptides generated by partial cleavage with N-chlorosuccinimide and by its failure to react with a monoclonal antibody directed against the large subunit of DNA polymerase alpha. The DNA polymerase is inhibited by 200 mM NaCl and is unable to use poly(rA)/oligo(dT) as a template, thus differentiating it from DNA polymerase gamma. On the basis of these properties, we propose that the DNA polymerase that we have purified from 0- to 2-hr Drosophila melanogaster embryos is DNA polymerase delta.